1998
DOI: 10.1023/a:1007925832420
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Abstract. This article presents a statistical theory for texture modeling. This theory combines filtering theory and Markov random field modeling through the maximum entropy principle, and interprets and clarifies many previous concepts and methods for texture analysis and synthesis from a unified point of view. Our theory characterizes the ensemble of images I with the same texture appearance by a probability distribution f (I) on a random field, and the objective of texture modeling is to make inference abou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 530 publications
(21 citation statements)
references
References 38 publications
0
21
0
Order By: Relevance
“…It has been pointed out by Zhu, Wu, & Mumford (1998) that, in principle, the marginal densities of Ðlter response are a complete set of statistics in the same sense that the N-point functions are completeÈgiven all the marginal densities, we would be able to reconstruct the probability density exactly. Following Zhu et al (1998), this is demonstrated by Ðrst taking the Fourier transform of the density for the Ðeld (we are assuming a discrete collection of sites j in a lattice V ),…”
Section: Importance Of Basis For Statistical Characterizationsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been pointed out by Zhu, Wu, & Mumford (1998) that, in principle, the marginal densities of Ðlter response are a complete set of statistics in the same sense that the N-point functions are completeÈgiven all the marginal densities, we would be able to reconstruct the probability density exactly. Following Zhu et al (1998), this is demonstrated by Ðrst taking the Fourier transform of the density for the Ðeld (we are assuming a discrete collection of sites j in a lattice V ),…”
Section: Importance Of Basis For Statistical Characterizationsmentioning
confidence: 99%
“…The information theoretic measure of distinguishability, as also emphasized in Zhu et al (1998), and known as the Kullback-Leibler (K-L) distance (Kullback 1959) between the marginal densities for a given process h(v) and the marginal density for the Gaussian process with the same power spectrum g (v), is given by…”
Section: Importance Of Basis For Statistical Characterizationsmentioning
confidence: 99%
“…We are investigating the Borrowed Strength Algorithm (BSA) [9] as a post-detection algorithm for the UCIR imagery. A partial differential equation based approach to image processing, anisotropic diffusion or nonlinear diffusion filtering [10][11][12][13][14][15][16], is being evaluated for use on the UCIR imagery. We are also looking at the use of blind deconvolution or phase retrieval approaches [17], although they tend to suffer from numerical difficulties [18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…In model-based methods, mathematical models are used to represent the textures in an image such as fractals (Xia et al, 2006), random field models (Zhu et al, 1998) and so on. Signal processing methods consider the frequency domain of the digital images for the texture feature extraction.…”
Section: Literature Review and Related Workmentioning
confidence: 99%